СИСТЕМА ПРАКТИЧНОЇ ПІДГОТОВКИ МАЙБУТНІХ УЧИТЕЛІВ ОБРАЗОТВОРЧОГО МИСТЕЦТВА У ВИЩОМУ ПЕДАГОГІЧНОМУ НАВЧАЛЬНОМУ ЗАКЛАДІ - Мужикова, Ірина (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті обґрунтовано систему практичної підготовки майбутніх учителів образотворчого мистецтва у вищих педагогічних навчальних закладах з позицій системного, інтегративного, особистісно-орієнтованого, компетентнісного та діяльнісного наукових підходів, презентовано рівневу модель, схарактеризовано цільовий (мета та завдання), змістовий (система практичних завдань), організаційно-процесуальний (навчально- методичне та організаційне забезпечення, система контролю та критерії оцінювання результатів) та результативний (вимоги до рівня практичної підготовки випускників) компоненти. В статье обоснована система практической подготовки будущих учителей изобразительного искусства в высших педагогических учебных заведениях с позиций системного, интеграционного, личностно ориентированного, компетентностного и деятельностного подходов, представлена уровневая модель, дана характеристика целевого (цель и задачи), содержательного (система практических заданий), организационно-процессуального (учебно-методическое и организационное обеспечение, система контроля и критерии оценивания результатов) и результативного (требования к уровню практической подготовки выпускников) компонентов. The system of practical training of future teachers of fine arts in higher pedagogical institution is discussed in the article. Interconnection and interdependence of formation of practical training from the perspective of systematic, integrative, person-centered, competence and active scientific approaches, tiered model of education, are shown on the basis of analysis of scientific sources on issues of professional training of specialists and formation of their professional competence, research in the field of fine arts education and regulatory framework, target (goals and objectives of practical training at every stage of its implementation), content (a system of practical fine arts tasks, educational, methodical, research and organizational work), organizational and procedural (educational, methodological and organizational information, system of control of academic performance and criteria for evaluation of results of practical activities of students) and result (requirements for level of practical training of graduates) structural components of the practical training are defined and characterized using the same basis. The author insists on the need to preserve the experience of the practical training of future teachers of fine arts during the higher education reforms.